A revolution in eating how the quest for food shaped America - McWilliams, James E. (Columbia Univ. Press, 2005)
History of food in the United States.
Includes bibliographical references and index
Keywords: Geschichte 1650-1850; Gastronomie; Voedingsgewoonten; aGastronomy -- xHistory; aFood habits -- zUnited States -- xHistory; Wertwandel; Sozialer Wandel; Ernährungsgewohnheit; USA